The volatile anesthetic isoflurane increases endothelial adenosine generation via microparticle ecto-5'-nucleotidase (CD73) release. - Mihwa Kim; Ahrom Ham; Katelyn Yu-Mi Kim; Kevin M Brown; H Thomas Lee (PLoS ONE, 2014)
Endothelial dysfunction is common in acute and chronic organ injury. Isoflurane is a widely used halogenated volatile anesthetic during the perioperative period and protects against endothelial cell death and inflammation. In this study, we tested whether isoflurane induces endothelial ecto-5'-nucleotidase (CD73) and cytoprotective adenosine generation to protect against endothelial cell injury. Clinically relevant concentrations of isoflurane induced CD73 activity and increased adenosine generation in cultured human umbilical vein or mouse glomerular endothelial cells. Surprisingly, isoflurane-mediated induction of endothelial CD73 activity occurred within 1 hr and without synthesizing new CD73. We determined that isoflurane rapidly increased CD73 containing endothelial microparticles into the cell culture media. Indeed, microparticles isolated from isoflurane-treated endothelial cells had significantly higher CD73 activity as well as increased CD73 protein. In vivo, plasma from mice anesthetized with isoflurane had significantly higher endothelial cell-derived CD144+ CD73+ microparticles and had increased microparticle CD73 activity compared to plasma from pentobarbital-anesthetized mice. Supporting a critical role of CD73 in isoflurane-mediated endothelial protection, a selective CD73 inhibitor (APCP) prevented isoflurane-induced protection against human endothelial cell inflammation and apoptosis. In addition, isoflurane activated endothelial cells Rho kinase evidenced by myosin phosphatase target subunit-1 and myosin light chain phosphorylation. Furthermore, isoflurane-induced release of CD73 containing microparticles was significantly attenuated by a selective Rho kinase inhibitor (Y27632). Taken together, we conclude that the volatile anesthetic isoflurane causes Rho kinase-mediated release of endothelial microparticles containing preformed CD73 and increase adenosine generation to protect against endothelial apoptosis and inflammation.